2011
DOI: 10.1017/s0008197311000560
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Dutch and Uk Judges Cite Foreign Law?

Abstract: The author wishes to thank the judges who participated in the interviews and the members of the HiiL Highest Courts Research Group for their comments and suggestions concerning earlier drafts of this paper. The usual disclaimer applies. 1 From a legal perspective, 'globalisation' can be defined as the trend toward world domination of specific regimes; see H.P. Glenn, Legal Traditions of the World (Oxford 2007), p. 49. The emergence of transnational connections between courts has been referred to under many dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…61 With the increased prominence of European law in the past decades, it could be that the comparative ethos ingrained into the institutional DNA of the Supreme Court was simply extended to citations of other European supreme courts. 62 In this European context, UK Supreme Court judges have reported that the prestige of the cited court is an important determinant of their willingness to cite, 63 which also in part explains the distribution of citations we have discovered. There are also more tangible ways in which the internationalized and Europeanized nature of the UK's (and particularly England's) legal order has manifested.…”
Section: B 'True Comparatists'mentioning
confidence: 87%
See 2 more Smart Citations
“…61 With the increased prominence of European law in the past decades, it could be that the comparative ethos ingrained into the institutional DNA of the Supreme Court was simply extended to citations of other European supreme courts. 62 In this European context, UK Supreme Court judges have reported that the prestige of the cited court is an important determinant of their willingness to cite, 63 which also in part explains the distribution of citations we have discovered. There are also more tangible ways in which the internationalized and Europeanized nature of the UK's (and particularly England's) legal order has manifested.…”
Section: B 'True Comparatists'mentioning
confidence: 87%
“…In response to questions of why they cite foreign decisions, some UK Supreme Court judges have reported that they felt a sense of duty to explain to the parties why their arguments were rejected, as well as a sense of duty to openly cite a foreign court as a matter of courtesy if they have followed the foreign court's reasoning. 59 In a similar vein, the House of Lordsthe UK Supreme Court's predecessorhas historically been a comparative institution, with a long tradition of consulting and referencing decisions of many other common law courts. 60 Citing foreign decisions has been institutionally encouraged.…”
Section: Uk (143)mentioning
confidence: 99%
See 1 more Smart Citation
“…Elaine Mak observing that "sources most often referred to come from Commonwealth legal systems and from the US legal system." 92 The very willingness of UK courts to invoke judicial decisions from other common law jurisdictions evinces some openness to learning from those countries. This suggests an acknowledgement that former colonies may have useful knowledge to impart to British institutions.…”
Section: A Common Law Unitymentioning
confidence: 99%
“…Mak's surveys of UK and Dutch Supreme Court Justices confirm that, in addition to legal tradition and language, prestige is one of the three main factors that influences the use of foreign law by those courts. 77 Flanagan and Ahern's 2006 survey of 43 superior court judges from common law countries (including three High Court Justices) similarly observes that 'some judges use comparative material to earn the professional approval of "respected" foreign judges'. 78 Prestige is, to some extent, an observable factor in the High Court's practice of following foreign decisions but it is difficult to draw firm conclusions as the Justices seldom refer to the perceived prestige of the foreign legal system in their reasons.…”
Section: B Prestigementioning
confidence: 99%